A continuous mitigation of kVAR-voltage problem of hybrid isolated power system using UPFC. Issue 1 (2nd January 2020) - Gandhar, Abhishek; Gupta, Sunil; Tiwari, Mohit; Gandhar, Shashi
Abstract: Electric power system in rural India is in growing stage but still many parts of country are not connected. Renewable Energy Sources (RES) based small power system can be beneficial for such locations. The fluctuations associated with renewable energy sources can be countered by Flexible AC transmission Systems (FACTS) devices. In this paper, Unified Power Flexible controller is used for studying the kVAR-voltage problem of test system. The proposed test system is a combination of conventional alternator and asynchronous generator representing diesel and wind energy system machines. A time-domain simulations is done in the proposed system considering variable speed conditions. This paper clearly presents the voltage-kVAR management capabilities of this controller. The detailed analysis of proposed multi-machine test system with UPFC has been done in SIM POWER SYSTEM/MATLAB software